Models of acceptance and use of technology research trends: Literature review and exploratory bibliometric study - Alturas, B. (2021)
Acceptance and Use of Technology Models suggest that some constructs predict behavioural intention towards the acceptance and use of technology. For this reason, these models are increasingly used by researchers around the world. At the same time, teachers of information technology and systems teach these models as part of the content of various courses. This study aims to analyse the publications of the last five years on Acceptance and Use of Technology Models. An exploratory bibliometric study was carried out, using the Proquest and Scopus platforms, in the period from 2014 to 2018, to find out which models are most used by researchers. The findings suggest that the number of articles into the top journals has increased, and that there is a wider array of journals publishing articles about this topic. Also, the study revealed that the most cited models were TPB and TAM.